IDENTIFICATION OF WIDE COMPATIBILITY VARIETIES IN SOME TROPICAL JAPONICA RICE - A. Hairmansis; Hajrial Aswidinnoor; Trikoesoemaningtyas Trikoesoemaningtyas; Suwarno Suwarno (Indonesian Agency for Agricultural Research and Development, 2005)
The F1 hybrid sterility in indica/japonica crosses is the major barrier in developing hybrid rice varieties between these two diverse germplasm. The sterility problem in japonica/indica hybrids can be overcome by using wide compatibility genes. The objective of this study was to identify wide compatibility varieties (WCVs) in some tropical japonica rice. Twenty five tropical japonica varieties as male parents were crossed with indica (IR64) and japonica (Akitakomachi) testers as female parents. The crosses were planted following a randomized complete block design with three replications. Varieties having average spikelet fertility of more than 70% with both the indica and japonica testers were rated as WCVs. Result from this study showed that six tropical japonica varieties were classified as WCVs, i.e., Cabacu, Grogol, Kencana Bali, Klemas, Lampung Lawer, and Napa. Hybrid sterility is caused by partial sterility of male and female gametes. The WCVs from the present study can be used in hybrid rice breeding program to solve hybrid sterility in indica/japonica hybrids.